Contextual and Situational Factors Determining Perceived Counselling Effectiveness of Professional Counselling Psychologists - Adekola Kamil Lasisi (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Effective guidance and counselling service is germane to the much-anticipated socio-economic development of Nigeria as a nation. Much is needed to be done to achieve effective Guidance and Counselling Services in the Nigerian school system. This study aims to analyze contextual and situational factors (age, gender, teaching experience and counselling experience) determining the perceived counselling effectiveness of selected professional counselling psychologists in Kwara State. The correlational Research method was adopted for this study. 120 randomly selected professional counselling psychologists were the participants of this study. The instrument of the study was the Perceived Counselling Effectiveness Determining Factor Scale (PCEDFS) using four Likert formats was used for this study. The generated data were subjected to Pearson Product Moment Correlation and Multiple Regression Analysis. The findings showed a significant relationship between each of the independent variables and the dependent variable; independent variables made a significant joint contribution to the prediction of the dependent variable and all the independent variables relatively made a significant contribution to the prediction of the dependent variable. The findings were discussed and necessary recommendations were highlighted. The implications of the findings for vocational and entrepreneurial development were explained.